Narrative Review: Communication and Decision-Making Dynamics Between Nurses, Paramedics, and Special Forces Teams in High-Stress Situations - Alotaibi, Abdulrhman Jameel; Abdullah Nasser Alotaibi; Saeed Abdulrahman Alahmari; Saeed Abdullah Aldosari; Turki Abdullah Aldosari; Sara Abdullah Aldosari; Abdullah Mohammed Altuwaijeri; Fahad Kanaan Almutairi; Mohammed Mishal Alotaibi; Shadeed Marzouq Masoud Alqahtani (Saudi Journal of Medicine and Public Health, 2024)
<span style="font-size: 12pt; font-family: ’Times New Roman’, serif; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: ’Times New Roman’, serif; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Effective response to high-stress emergencies like mass casualty incidents relies on seamless collaboration among nurses, paramedics, and special forces medics. Their distinct professional cultures and protocols, if unaligned, can create dysfunctional dynamics that compromise outcomes. <span style="font-size: 12pt; font-family: ’Times New Roman’, serif; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: ’Times New Roman’, serif; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This review synthesizes evidence (2010-2024) on communication, decision-making, and collaboration dynamics among these personnel in emergency scenarios, identifying barriers and facilitators to effective teamwork. <span style="font-size: 12pt; font-family: ’Times New Roman’, serif; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: ’Times New Roman’, serif; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive search across PubMed, CINAHL, PsycINFO, and military databases was conducted. Included qualitative studies, reviews, and simulations were thematically analyzed. <span style="font-size: 12pt; font-family: ’Times New Roman’, serif; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: ’Times New Roman’, serif; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Key themes include: contrasting professional paradigms (holistic vs. protocol-driven vs. mission-tactical); communication barriers under stress (jargon, overload); a shift to intuitive decision-making; and critical enablers like shared mental models and cross-training. <span style="font-size: 12pt; font-family: ’Times New Roman’, serif; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: ’Times New Roman’, serif; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Genuine interoperability requires pre-event joint training, standardized communication (e.g., SBAR), and mutual role understanding. Investing in these "soft skills" is as vital as technical proficiency.